Workshop penguatan pembelajaran K13 dan konsep dasar matematika pada Kelompok Kerja Guru SD (KKG) Gugus IX Kecamatan Ujung Kota Parepare - Hasnah Hasnah; Zaid Zainal; Muslimin Muslimin (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The Partnership Program (PKM) is a Teacher Working Group (KKG) for Elementary School IX in district Ujung cityParepare , which is divided into 6 schools namely, SDN 5, SDN 1, SDN 55, SDN 29, SDN 30 and SD Muhammadiyah 3. Theproblem is ; (1) Teacher Competency Test (UKG) results in Parepare are still low, (2) Elementary school teachers' mastery ofmathematics material is still low, (3) Teacher's understanding of the curriculum is still lacking. The method used to overcome theabove problems by carrying out workshops proposed to high-grade teachers aimed at: (1) approval of understanding to membersof the KKG about the 2013 revised special curriculum (2) increasing the knowledge / understanding of KKG members about thebasic concepts of mathematics, ( 3)) Assist KKG members in solving math problems that are considered difficult. The resultsobtained from the revised K-13 learning kit from all grade levels (IV - VI) made by all participants. Other results obtained consistof elementary math problems and solving which are often considered difficult by students and teachers.